Privileged wills in Malaysia: the sustainability of privileged wills among soldiers, airmen and sailors - Hussain, Faridah; Mohd Kamal, Mohd Hisham; Halim, Akmal Hidayah; Ahmad Bustami, Tajul Aris (PKP Publishing Services, 2016)
Privileged will is the right of soldiers and airmen, and sailors, to dispose of their property during “actual military service”, and “at sea”, respectively. The sustainability of this right leads to economic prosperity and social justice. The objective of this paper is to examine the sustainability of privileged wills as a model for combating poverty among soldiers, airmen and sailors in Malaysia. Privileged wills appear to be relevant and important as soldiers, airmen and sailors may dispose of their properties during difficulties in obtaining advice and assistance to make a formal will. Despite the benefit, it is found that the legal provisions relating to privileged wills are not applicable to Muslims and native soldiers and sailors, and that there is no clear legal provision to guide Muslims and native soldiers and sailors to make privileged wills. The methodology employed in discussing this paper is a qualitative research using doctrinal and comparative approach to the legal systems. This paper analyses legislations governing privileged wills ranging from the Malaysian Wills Act 1959 (Act 346), the Sabah Wills Ordinance (Sabah Cap. 158), Armed Forces Act 1972 (Act 77) and the English Wills Act 1837. The study suggests that the Government of Malaysia should support the idea to extend the provision of law on privileged wills to Muslim and native soldiers and sailors. This is to enable the society to earn and benefit from the property disposed of by soldiers, airmen and sailors.